2010
DOI: 10.3109/09286586.2010.528853
|View full text |Cite
|
Sign up to set email alerts
|

Shorter Axial Length and Increased Astigmatic Refractive Error are Associated With Socio-Economic Deprivation in an Adult UK Cohort

Abstract: Axial length and astigmatic refraction were inversely associated with socio-economic deprivation in this population. Identification of the environmental exposures involved may identify reversible risk factors for impaired vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Socioeconomic status is defined by several factors such as parental education, employment, income, accessibility of services, school fees (private vs government), and housing type [ 187 , 263 265 ]. A large-scale study in China found a positive correlation between myopia and higher socioeconomic status indicators such as urban living, owning property, and duration of education [ 266 ].…”
Section: Environmental Factors Influencing Myopiamentioning
confidence: 99%
“…Socioeconomic status is defined by several factors such as parental education, employment, income, accessibility of services, school fees (private vs government), and housing type [ 187 , 263 265 ]. A large-scale study in China found a positive correlation between myopia and higher socioeconomic status indicators such as urban living, owning property, and duration of education [ 266 ].…”
Section: Environmental Factors Influencing Myopiamentioning
confidence: 99%
“…Previous studies have found many factors associated with astigmatism including high risk genes, eyelid pressure, extraocular muscle tension, gestational age, birth weight, nutrition [1], ethnicity, spherical equivalent refractive error, maternal smoking during pregnancy [2], accommodative convergence/accommodation ratio (AC/A) [3], age, education, ametropia [4], the axial length-corneal radius ratio (AL/CR) [5], delivery mode [6], socio-economically deprivation [7] and iris color [8]. In a recent paper on 48-60-month-old Chinese children [9], we reported the prevalence of the components of astigmatism, described the difference between corneal astigmatism (CA) and anterior corneal astigmatism (ACA), and demonstrated the compensatory role of internal astigmatism (IA) in reducing ACA.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the studies comparing visual acuity and socioeconomic situation described above do not adjust for coexisting eye disease (apart from previous cataract surgery and uncorrected refractive error by Yip et al (2013)), so there may be some overlap with associations described in the following sections of this article. Goverdhan et al (2011) found that socioeconomic disadvantage was associated with shorter axial length (0.24mm difference between the highest and lowest IMD quintiles) and greater astigmatism (0.12 dioptres (D) difference between the highest and lowest quintiles), but not with spherical refraction. The absence of an association with spherical refraction and the level of difference in astigmatism would suggest that there is no clinically significant association here.…”
Section: Reduced Visual Acuity (Va)mentioning
confidence: 96%